FRI0135 Is statin use in patients with rheumatoid arthritis consistent with EULAR recommendations?. (23rd January 2014) - Eidner, T.; Neumann, T.; Wolf, G.; Oelzner, P.
Abstract : Background: According to the EULAR recommendations for cardiovascular (CV) risk management in patients with rheumatoid arthritis (RA), statins belong to the preferred treatment options. Objectives: To evaluate statin use in RA patients in daily practice in comparison to EULAR recommendations according to individual cardiovascular risk. Methods: We studied 245 consecutive patients with rheumatoid arthritis from our university rheumatological outpatient department. The following data were collected: age (>40 years), gender, duration of disease, RF/CCP-antibody-status, lipid-status, blood pressure/use of antihypertensive drugs, comorbidities (diabetes mellitus – Dm, cardiovascular diseases), smoking history, use of statins. For RA patients with Dm or established cardiovascular disease (Coronary heart disease, peripheral or cerebrovascular arterial occlusive disease) an indication for statin use was postulated. In patient without these comorbidities, an indication for statin use was supposed in case of a 10-year-risk for cardiovascular events of at least 10% according to the SCORE-algorithm [1] and the EULAR-recommendations [2]. Results: Diabetes mellitus and/or a cardiovascular disease were comorbidities in 62 of 245 RA patients (25, 3%; f/m 35/27); 37 of them were treated with statins (59, 7%). In 183 patients without these comorbidities the assumed 10-year-risk for severe cardiovascular events according to the SCORE-algorithm accounted for: – at least 15% in 16 pts. (8, 7%), – between 10 and 15% in 30 pts. (16, 4%), – between 5 and 10% in 59 pts. (32, 3%) and – under 5% in 78 pts. (42, 6%). From 46 pts. with a risk-score of at least 10% only 7 pts. (15, 2%) were treated with statins. Conclusions: In RA patients with diabetes mellitus or established cardiovascular disease, statins are a common comedication. In contrast, in patients without these comorbidities but with high cardiovascular risk statins are only rarely used. In consideration of the increased cardiovascular risk of RA patients and the current treatment recommendations, every patient should be examined for the individual cardiovascular risk including reassessing the indication for statin use at least yearly. Therefore, a tight cooperation between rheumatologist and general practitioner is required. References: Conroy et al.; Eur Heart J 2003;24:987–1003. Peters et al.; Ann Rheum Dis 2010 69: 325-331. Disclosure of Interest: None Declared